Exploring Organizational Climate on Transportation Department in West Bandung Regency - Senen Machmud (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
This study explores the factors that shape the organizational climate in one of the government agencies that deal with the field of transportation in West Bandung Regency. The research method uses a cross-section approach that uses 71 respondents in one government agency in West Bandung Regency. Data analysis techniques used Exploratory Factor Analysis (EFA) to validate the factors that make up the organizational climate. The results show that there are 3 (three) factors that make up the organizational climate, namely Situation and Rules, Relationships, and Work, that can explain 55.73% of the overall research instrument.